Moderation of alcohol consumption as a recommendation in European hypertension management guidelines: a survey on awareness, screening and implementation among European physicians. Issue 10 (21st October 2018) - Zaidi Touis, Laila; Bolbrinker, Juliane; Riemer, Thomas Günther; Kreutz, Reinhold
Abstract : Objectives: Moderation of alcohol consumption is included as a class I, level of evidence A recommendation in the current European guidelines for the management of hypertension. We investigated its awareness and self-reported implementation among European physicians across different specialties and workplaces. Design and setting: A cross-sectional survey study conducted in two annual German meetings (German Society of Cardiology and the German Society of Internal Medicine) and two annual European meetings (European Society of Hypertension and European Society Cardiology) in 2015. Participants: 1064 physicians attending the European meetings were interviewed including 52.1% cardiologists, 29.2% internists and 8.8% general practitioners. Main outcome measures: Physician screening of alcohol consumption, awareness and self-implementation of the recommendation of the current European guidelines about moderation of alcohol consumption for the management of hypertension. Results: Overall, 81.9% of physicians reported to generally quantify alcohol consumption in patients with hypertension. However, only 28.6% and 14.5% of participants reported screening alcohol consumption in their patients with newly detected or treatment-resistant hypertension. Physicians recommended a maximum alcohol intake of 13.1±11.7 g/day for women (95% CI 12.3 to 13.8) and 19.9±15.6 g/day for men (95% CI 18.8 to 20.9). In case of moderate to high alcohol consumption, 10.3% would manage only hypertension without addressing alcohol consumption, while 3.7% of the physicians would do so in case of alcohol dependence (p<0.001). Conclusions: The average amount of alcohol intake per day recommended by European physicians in this survey was in agreement with the guidelines. The low number of physicians that screen for alcohol consumption in patients with newly detected and with treatment-resistant hypertension indicates an important deficit in the management of hypertension.